What's in a Name?: Effects of Category Labels on the Consumers' Acceptance of Robotic Products - Jun San Kim; Sona Kwak; Kang, Dahyun; JongSuk Choi (PROCEEDINGS OF THE 2020 ACM/IEEE INTERNATIONAL CONFERENCE ON HUMAN-ROBOT INTERACTION (HRI '20), 2020)
A study was conducted to investigate the effects of category labels of domestic robots on their consumer acceptance. The authors posited that compared to the label robots, a pre-existent category label such as home appliances would increase the consumers' evaluation of and purchase intention towards the products. It is suggested that the pre-existent category label helps consumers to perceive the functional values they stand to gain by consuming the product more than the label robots, which is often related to the concepts generated around cultural artifacts. The results of the study confirmed the hypotheses, and further discussions are provided in this paper.
Keywords: Robotic products; consumer value and acceptance; category labels